The Implementation of Family Centered Care in Hypertensive Patients at Private Clinic - Say, Yosefina Dwikurnia Gufra Putri; Arya, Insi Farisa Desy; Amelia, Indah (Faculty of Medicine, Public Health, and Nursing, 2023)
Hypertension is a condition when a person has systolic blood pressure ≥140 mmHg and/or diastolic blood pressure ≥ 90 mmHg when measured at a clinic or health facility. Hypertension can be a risk factor of important organs damage such as the brain, heart, kidneys, retina, large blood vessels (aorta) and peripheral blood vessels. To prevent the complications, hypertensive patients must control their blood pressure. One approach to achieving controlled blood pressure is involving the family in hypertension management, which is called Family Centered Care. This approach has been implemented at Mitra Sehati Clinic, a private clinic located in Bandung Regency, West Java. This study aims to determine the implementation of hypertension management using the Family Centered Care approach at Mitra Sehati Clinic. This research is a qualitative research using a single case study method. The data were obtained through in-depth interviews, observation and documentation and then analyzed using interpretive analysis methods in which emerging themes were interpreted based on the theory of Family Centered Care and hypertension so they became the basis for describing certain conclusions. The results obtained show that all elements of Family Centered Care in the management of hypertension have been carried out by health workers at the Mitra Sehati Clinic which are also included in several programs. In addition, a positive impact was found on patients, their families and health workers. However, in its implementation, obstacles were found, it was limited time. The solution was to use online consultations via the doctor's or nurse's personal cellphone number. Implementation of Family Centered Care in the management of hypertension has a good impact on patients, their families and health workers.